Addition of Zirconium Oxide for Reduction of Hydroxyapatite Layer Cracks in Ti-6Al-4V ELI Implant Materials for Improved Osseointegration - Sanny Ardhy; Gunawarman Gunawarman; Jon Affi; Yuli Yetri (Department of Mechanical Engineering, Universitas Andalas, 2022)
The hydroxyapatite (HA) layer on the surface of the implant material tends to crack during the sintering process for layer densification. This causes the process of implant union with bone (osseointegration) does not function perfectly in the human body. This study aims to reduce cracking by increasing the adhesion of the HA layer on the surface of the Ti-6Al-4V Extra Low Intertitial (ELI) implant material. The research used the dip coating method to get a thin and even layer. To strengthen the adhesion of the coating, Zirconium Oxide (ZrO2) was added in commercial HA suspension. The test specimens were heated at sintering temperatures of 800 0C, 900 0C and 950 0C with a heating rate of 5 0C /minute. Layer morphology and cracks were seen using an optical microscope. The percentage of layer cracks will be measured using ImageJ software. The results obtained, the addition of ZrO2 can reduce cracks in the HA layer of the surface of the test specimen. The percentage of cracks decrease with the addition of ZrO2 (17% and 20% weight) to the suspension of the HA layer. These result is certainly good for increasing osseointegration in the human body.